Factors influencing performance of aircraft safety procedures and perceptions of accident survivability - Fennel, P. J. (Cranfield University, 1992)
The primary objectives of the research programme described in this thesis ( and commissioned by the United Kingdom Civil Aviation Authority) were to evaluate the effectiveness of safety cards for communicating safety information to passengers and to assess the influence of possible alternative styles of safety briefing on passenger attention. These objectives were investigated in two separate simulated pre-warned ditching situations on board a stationary aircraft. Participants' knowledge of the less complicated aspects of safety information, such as the location of oxygen masks or how to inflate the lifejacket, was generally high but comprehension of more complex procedures, such as the correct method of donning the lifejacket, was more limited. A visual demonstration was shown to significantly increase the likelihood that participants would know the correct method of donning the lifejacket, operating the oxygen mask and adopting the brace position correctly. A number of human factors problems, most frequently due to lack of specific information, were also identified as adversely affecting participants' ability to carry out safety procedures. Passengers' motivation to pay attention to safety information would be likely to be enhanced if briefings were more meaningful to them, for example, personalised and less repetitive, or if they were given the opportunity to practise safety procedures in a low stress situation. Participants' opinions indicated that emphasis on the importance of passengers knowing how to operate i terns of safety equipment would not put the majority of passengers off flying and would be likely to encourage attention to safety briefings and cards. The evaluation of the safety cards and briefings indicated that no one card or briefing was more effective overall. Some general principles for the design of safety cards have been suggested, such as the consultation with non-aviation personnel when designing safety cards and the inclusion of brief statements to explain complex procedures. The lack of major differences between the safety briefings may be attributable to the conventional manner in which they were presented suggesting that a different type of presentation style, for example one which personalises or makes the information more meaningful to passengers, would be more likely to encourage attention. A secondary objective of the thesis was to explore the influence of perceived locus of control on passenger comprehension of safety information and on their perceptions of aircraft accident survivability. This was investigated in a survey of airline passengers in addition to the two simulated ditchings. Analysis of a specifically designed locus of control questionnaire indicated that locus of control had only a slight influence on participants' knowledge of safety information and on their perceptions of aircraft accident survivability. The dominant cultural image of aircraft accidents as being non-survivable would appear to obscure any possible influence of locus of control as a predictor of passenger emergency behaviour. Locus of control would appear to be more effectively utilised in situations where cultural definitions are less dominant and perceptions of chance and skill influences are more equally balanced. Air travel was considered to be the safest form of transport but aircraft accidents were perceived to be less survivable than accidents involving other forms of transport. Participants also tended to underestimate their chances of survival in a range of potential aircraft accident situations. In order to improve the accuracy of passengers' perceptions of aircraft accident survivability a more realistic image of aircraft safety is needed. The stability of perceptions of locus of control and the survivability of aircraft accidents observed in the participant groups indicates that attitudes and beliefs are firmly entrenched in the general population and that major efforts will be required to influence attitudes and beliefs. Any attempt to change attitudes towards aircraft accident survivability would need to begin with improving the media image as the media are the most influential information source in forming public opinion regarding accident survivability.